2006
DOI: 10.1002/clc.4960290208
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular pacing reduces ventricular arrhythmic burden and defibrillator therapies in patients with heart failure

Abstract: SummaryBackground: Cardiac resynchronization therapy (CRT) has recently emerged as a new modality for the treatment of patients with advanced heart failure (HF).Hypothesis: Cardiac resynchronization therapy reduces atrial and ventricular arrhythmia burdens.Methods: We analyzed the clinical data of patients who underwent an upgrade from a dual-chamber to a biventricular implantable cardioverter-defibrillator (ICD) at a tertiary care center.Results: Nineteen patients (age 67 ± 10 years, 18 men, left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…9 Interestingly, in patients having a stroke, which is well known to cause an increased sympathetic tone 33 and impaired parasympathetic function 34 both of which are predisposing factors for sudden cardiac death, 35 impaired longitudinal function of the inferior wall has been demonstrated to be the strongest echocardiographic predictor of outcome. 29 Several studies have indicated that CRT treatment reduces the risk of VT/VF [36][37][38][39] ; however, other studies have shown a proarrhythmic effect of CRT. [40][41][42] The mechanism by which CRT has been thought to reduce the risk of VT/VF has been attributed to the improved hemodynamic status and LV reverse remodeling.…”
Section: Myocardial Deformation and Prognosismentioning
confidence: 99%
“…9 Interestingly, in patients having a stroke, which is well known to cause an increased sympathetic tone 33 and impaired parasympathetic function 34 both of which are predisposing factors for sudden cardiac death, 35 impaired longitudinal function of the inferior wall has been demonstrated to be the strongest echocardiographic predictor of outcome. 29 Several studies have indicated that CRT treatment reduces the risk of VT/VF [36][37][38][39] ; however, other studies have shown a proarrhythmic effect of CRT. [40][41][42] The mechanism by which CRT has been thought to reduce the risk of VT/VF has been attributed to the improved hemodynamic status and LV reverse remodeling.…”
Section: Myocardial Deformation and Prognosismentioning
confidence: 99%
“…31 Cases have been reported of CRT inducing ventricular arrhythmias, but several trials report a reduction in these events. [32][33][34][35][36] A review of the 2 largest CRT trials did not show significant increases or decreases in ventricular arrhythmia. 37 …”
Section: Patient Selection and Therapeutic Resultsmentioning
confidence: 99%
“…Some studies have suggested an anti-arrhythmic effect of BIV pacing16, 17 while others have reported a pro-arrhythmic effect from BIV pacing18, presumably due to pacing very close to the reentrant circuit in the LV, thus facilitating the induction of reentrant ventricular arrhythmias. Whether the shorter repolarization time documented in our rabbit model, albeit in a normal heart, constitutes one of the mechanisms of reduced ventricular arrhythmia burden with BIV pacing in heart failure patients remains unclear but deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%